Connecting South Asia and Southeast Asia (Book collections on Project MUSE., 2016)
This report analyzes how closer regional connectivity and economic integration between South Asia and Southeast Asia can benefit both regions, with a focus on the role played by infrastructure and public policies in facilitating this process. It examines major developments in South Asian-Southeast Asian trade and investment, economic cooperation, the role of economic corridors, and regional cooperation initiatives. In particular, it identifies significant opportunities for strengthening these integration efforts as a result of the recent opening up of Myanmar in political, economic, and financial terms. This is particularly the case for land-based transportation--highways and railroads--and energy trading. The report's focus is on connectivity in a broad sense, covering both hardware and software, including investment in infrastructure, energy trading, trade facilitation, investment financing, and support for national and regional policies.